التنبؤ بالتعثر المالي من خلال أسلوبي التحليل التمييزي واللوجستي -دراسة حالة بنك التنمية المحلية) ( والبنك الوطني الجزائري) - مريم بوقطف; نور الهدى علالقة (My University, 2022)
The future of any company and its continuity based on its financial position and profits, in addition to its ability to face the events, the liquidity available at the company and its capacity to settle its debts. It is very important to focus on this subject of company distressed. This study attempted to answer the problem of how effective are the discriminatory and logistic analysis methods predicting financial failure? By relying on the descriptive approach in the theoretical aspect to present some concepts related to the topic of the research such as financial stumbling, financial hardship, financial failure, bankruptcy, and the case study approach in the practical aspect by applying to a group of institutions that represent the field of study, through the use of the method of discriminatory analysis And the logistic method, and the use of the comparative approach to highlight the similarities and differences between the two methods, as well as to determine which of them is better in predicting the financial failure of institutions.economic . The study produced results, the most important of which is the high ability to predict financial failure using the method. .............................................. يعتمد مستقبل أي مؤسسة واستمراريتها على وضعها المالي ومدى تحقيقها للأرباح، بالإضافة إلى مدى قدرتها على مواجهة الأحداث المستقبلية، والاحتفاظ بسيولة ملائمة و قدرتها على مواجهة الديون، لذلك أصبح موضوع التنبؤ بالتعثر المالي للمؤسسات أمرا من الضروري الاهتمام به. حاولت هذه الدراسة الإجابة على الإشكالية المتمثلة في ما مدى نجاعة أسلوبي التحليل التمييزي و اللوجستي في التنبؤ بالتعثر المالي،وذلك بالاعتماد على المنهج الوصفي في الجانب النظري لتقديم بعض المفاهيم المرتبطة بموضوع البحث كالتعثّر المالي، العسر المالي، الفشل المالي، الإفلاس، ومنهج دراسة الحالة في الجانب التطبيقي وذلك بالتطبيق على كل من بنك التنمية الحملية ا ولبنك ال وطني الج ا زئ ري اللذان يمثلان ميدان الدراسة، وذلك من خلال استعمال أسلوب التحليل التمييزي وأسلوب الإنحدار اللوجستي ، واستعمال المنهج المقارن لإبراز أوجه التشابه والاختلاف بين الأسلوبين، وكذا لتحديد أي منهما الأفضل في التنبؤ بالتعثر المالي. وأسفرت الدراسة عن نتائج أهمها القدرة العالية للتنبؤ بالتعثر المالي باستخدام أسلوب التحليل اللوجستي مقارنة بأسلوب التحليل التمييزي